(untitled) (Journal of Architectural Design, 2024)
In Nowadays, life in a modern city is filled with noise, people’s lives are saturated with a huge number of sounds from public transport, cars, and in homes - from the noise of air conditioners, elevators, etc. The constant presence of noise over 60 dB (decibels) is irreversible and leads to damage to people’s hearing organs. To reduce noise and improve sound insulation, it is necessary to use soundproofing materials and structures